Ventilación mecánica por distres respiratorio en paciente masculino de 70 años de edad con lesión cerebral aguda. - Cepeda Toapanta, Jorge Joel (2020)
The adult patient corresponds to neurological pathologies, has a longer stay on mechanical ventilation and a higher degree of mortality, considering that mechanical ventilation by itself is capable of inducing or aggravating the underlying pulmonary involvement. The patient with acute brain injury is at greater risk of developing aspiration pneumonia, neurogenic pulmonary edema, acute lung injury and acute respiratory distress syndrome, correct management of mechanical ventilation is essential on this occasion of acute brain injuries have acute respiratory syndrome. The acute respiratory distress syndrome manifesting in the patient in serious condition or with significant brain injury is usually fatal and the risk increases with age and severity of the disease people with acute respiratory syndrome suffer from serious difficulties in breathing and generally cannot Breathing on your own without the support of ventilatory support The treatment consists of supplying oxygen, controlling arterial fluids and gases. The objective of this study is to describe the management of mechanical ventilation in acute respiratory distress syndrome in patients with acute brain injury. Considering the increasingly frequent incorporation of new ventilation strategies such as ventilation in the prone position (PDV), ventilation with high frequency oscillation (HFOV), and the concept of open lung, we refer to the role of this technique in this adult patient.